1999
DOI: 10.1016/s1352-2310(98)00199-x
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence for the impact of the lake breeze circulation on ozone concentrations in Southern Ontario

Abstract: Very rapid increases in the concentrations of ozone and ozone precursors, in the late afternoon, have been observed at a rural and an urban site in southern Ontario. Ozone concentration increases of 30 ppbv in a few minutes have been observed. These increases occur simultaneously with the arrival of a Lake Ontario lake breeze front as identified from meteorological measurements and visible satellite imagery. This indicates that polluted air masses from over Lake Ontario are being transported inland by the lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 19 publications
2
34
0
1
Order By: Relevance
“…Dynamics at the lake-breeze front have been studied to understand effects on pollutants. Hastie et al (1999) noted that the arrival of the lake breeze coincided with maximum trace gas concentrations with rapid decreases behind the front suggesting that vertical mixing generated by the front could result in entrainment of cleaner air from above the inflow layer. Kitada and Kitagawa (1990) showed that the vertical profile of pollutants was strongly impacted by the micro-scale features of the sea breeze such as the transport of pollutants in the downdraft behind the front and suggested that the most aged air mass would be found in the upper part of the circulation behind the front.…”
Section: Distribution and Evolution Of Trace Gases And Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dynamics at the lake-breeze front have been studied to understand effects on pollutants. Hastie et al (1999) noted that the arrival of the lake breeze coincided with maximum trace gas concentrations with rapid decreases behind the front suggesting that vertical mixing generated by the front could result in entrainment of cleaner air from above the inflow layer. Kitada and Kitagawa (1990) showed that the vertical profile of pollutants was strongly impacted by the micro-scale features of the sea breeze such as the transport of pollutants in the downdraft behind the front and suggested that the most aged air mass would be found in the upper part of the circulation behind the front.…”
Section: Distribution and Evolution Of Trace Gases And Particlesmentioning
confidence: 99%
“…Specifically, a number of studies have been conducted in the Great Lakes area to examine lake breezes and their influence on air quality (e.g. Biggs and Graves, 1962;Lyons, 1972;Lyons and Cole, 1976;Reid et al, 1996;Sills 1998;Hastie et al, 1999). The region of southwestern Ontario often experiences poor air quality due to elevated O 3 and particulate matter (PM) concentrations (OME, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of this early work (e.g., Yap et al, 1988) suggested that local impacts on ozone levels were generally small, while some noted a more significant impact (Mukammal et al, 1982(Mukammal et al, , 1985. Ozone concentration increases of 30 ppbv over the course of a few minutes were linked through surface station and satellite observations to the passage of a lake-breeze front in a later, more detailed analysis (Hastie et al, 1999). Time-coincident aircraft measurements of precursor NO x and VOCs suggested that the air mass associated with the ozone maximum was well-aged and had moved inland from a position originating over Lake Ontario.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, a concentração temporal desse poluente é significativamente acompanhada das condições meteorológicas, incluindo a radiação solar, temperatura do ar, umidade relativa, precipitação e velocidade e direção do vento (Hastie et al, 1999;Kovač--Andrić, Brana & Gvozdić, 2009). O O 3 , no nível da superfície, tem efeitos negativos sobre a saúde humana, tais como dor de cabeça, irritação nos olhos, infecção respiratória e inflamação dos pulmões, bem como sobre a agricultura (Ashmore, 2005;Pinto, Blande, Souza, Amnerg & Holopainen, 2010).…”
Section: Introductionunclassified